Comparative Analysis of Divorce in the Perspective of Islamic Law and Indonesian Positive Law - Muniruddin Ritonga (AT-TAFAHUM: Journal of Law, 2026)
Divorce is a form of marital breakdown that is recognized in Islamic law and positive law in Indonesia. Although they have the same goal as a last resort in resolving domestic conflicts, the two legal systems have differences in setting legal terms, procedures, and consequences. This study aims to analyze divorce arrangements from the perspective of Islamic law and positive Indonesian law and examine their legal implications on the rights and obligations of the parties after divorce. The research uses normative legal methods with a legislative approach and a conceptual approach. Legal materials are obtained through literature studies which include laws and regulations, Compilations of Islamic Law, books, and scientific journals related to marriage law. All legal materials are analyzed qualitatively using descriptive-analytical methods. The results of the study show that Islamic law and positive law in Indonesia both place divorce as a last resort after peace cannot be realized. The difference lies in the implementation mechanism, where Indonesia's positive law requires that every divorce be decided through a Religious Court as a form of legal protection for the parties. Research also shows that divorce has legal consequences for child custody, alimony, and the rights and obligations of ex-spouses. Therefore, the harmonization between the principles of Islamic law and positive Indonesian law is an important factor in realizing legal certainty, justice, and protection of the rights of the parties after divorce.